2010
DOI: 10.1093/rfs/hhq123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Bank Intervention on the Interbank Market During the Subprime Crisis

Abstract: We explore whether central bank intervention improves liquidity in the interbank market during the current sub-prime crisis with unique trade and quote data from the e-MID, the only regulated electronic interbank market in the world. Central bank intervention consistently creates greater uncertainty in the interbank market. Prior to the crisis, the cover-to-bid ratio effectively conveys good and bad news from the central bank, but this link is broken during the crisis, suggesting that standard (and special) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 37 publications
1
57
0
Order By: Relevance
“…In particular, our results find that long memory approaches, represented by ARFIMA(p,d,q) models where d is the order of integration, provide superior fit-measures and statistically outperforms, in terms of point and density forecasting, random walk, autoregressive and moving average models during periods of high volatilities. Brunetti et al (2011) do not find mean reversion, but their linear specifications might not capture high persistence and nonstationarity modelled by our ARFIMA model. Moreover, our more recent sample where the intraday interest rates reduce in the final part of the sample and lower frequency data could explain the difference.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In particular, our results find that long memory approaches, represented by ARFIMA(p,d,q) models where d is the order of integration, provide superior fit-measures and statistically outperforms, in terms of point and density forecasting, random walk, autoregressive and moving average models during periods of high volatilities. Brunetti et al (2011) do not find mean reversion, but their linear specifications might not capture high persistence and nonstationarity modelled by our ARFIMA model. Moreover, our more recent sample where the intraday interest rates reduce in the final part of the sample and lower frequency data could explain the difference.…”
Section: Introductionmentioning
confidence: 74%
“…Baglioni and Monticini (2012) build up a simple model to explain why in normal times the only friction in action is related to settlement procedures and to the cost of central bank intraday credit (see the above references and VanHoose (1991)), while a liquidity crisis introduces a second component related to the chance of an upward jump of the intraday rate within the day due to some news (e.g., liquidity problems for some players in the market). Furthermore, Brunetti et al (2011) find that central bank interventions during the recent crisis introduced uncertainty and pushed up the intraday money market rate further than (negative) economic news. Durré and Nardelli (2008) show that money market rates have been more sensitive to fine-tuning operations in recent years and Brunetti et al (2011) claim that central banks either did not fully grasp the crowding effect, meaning commercial banks replace money market liquidity with central bank liquidity so that market conditions did not improve, see Heider et al (2009), or consistently underestimated funding liquidity demand.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Allen et al (2009), Affinito (2013, Brunetti et al (2011), Acharya et al (2012) and Gale and Yorulmazer (2013). Our results may therefore be of general interest.…”
Section: Introductionmentioning
confidence: 53%
“…Beirne et al (2011) study the impact of the first covered bond purchase programme on bond markets. Brunetti, di Filippo, and Harris (2011) find that the non-standard monetary programs lead to higher uncertainty in money markets. Abbassi and Linzert (2012) investigated the impact of ECB's non-standard monetary policy measures on interbank rates and found that it was effective in decreasing Euribor rates by more than 80 bps.…”
Section: Introductionmentioning
confidence: 88%